TOURISM COMMUNICATION MANAGEMENT OF UMBUL MADIUN TOURISM PARK - Muslih Aris Handayani (Institut Agama Islam Negeri (IAIN) Ponorogo, 2021)
The communication process can be interpreted as the transfer of information or messages from sending messages as communicators 1 and to the recipient of the message as communicator 2. In the process, communication aims to achieve mutual understanding between the two parties involved in the communication process. In various aspects of communication life is the most dominant activity whether it is in the form of providing information, motivation, or influence so that a person or group will follow the direction of a person or organization. Management is needed by all organizations, because without management all efforts will be wasted and achieving goals will be more difficult. Communication management as the basis in reformulating the communication management model conducted by umbul Madiun tourism center manager in dealing with problems both in the tourist workshop and outside problems faced by the tourist attractions This research is interpretive qualitative research to find patterns, models, or propositions. The data analysis in this study is inductive. Qualitative research will not produce generalizations but models. The results showed the process of tourism communication management involves the role of PR, group communication, mass communication and destination branding. Management and communication barriers in marketing are more pronounced in the technical aspects of improving the marketing of Umbul Madiun tourist park. Modernization of marketing technology, budget, and human resources limitations are also slow marketing processes. At the level of tourism communication management brand destination brand zoo facilities play, baths, swimming pools, amusement parks and others obstacles that arise, among others, the difficulty of designing a good brand of zoo facilities, entertainment and play venues, baths and swimming pools, as well as other facilities that are suitable for all ages and groups. At the level of tourism communication management on the scope of transportation communication obstacles that arise include realizing visitors or tourists to use the vehicle well and environmentally friendly. The limitations of parking lots on weekends are very difficult and it takes hard work to organize visitor vehicles well. At the level of tourism communication management in the scope of visual communication, obstacles that arise include limitations in designing pamphlets, brochures, banners, or travel book guides that are able to adopt all age groups or social status. At the level of tourism communication management on the scope of group communion, the problems that arise include designing a message that is able to accommodate all groups and social status at the level of Focus Group Discussion (FGD). At the level of communication management of internet media tourism (online) obstacles that arise include the ability to design internet messages that are friendly to all ages and social status or class. At the level of tourism communication management the scope of PR (PR) obstacles that arise include forms and models of cooperation between institutions to unite various interests. As a tourist attraction under the auspices of the tourism office, Umbul Madiun tourist park is subject to the rules of the tourism and culture office of Madiun Regency. A tug of interest sometimes occurs.